The State in New Zealand, 1840-198 : Socialism without Doctrines?. - Bassett, Michael (Auckland University Press, 2013)
In this innovative study Michael Bassett, historian and former politician, explores how and why the state became such an active and interventionist player in New Zealand life, developing, subsidising and regulating the economy and protecting citizens from the cradle to the grave. He looks in detail at the many schemes in which a paternalistic government became involved, especially the extensive social programmes. These were taken for granted by the people but from the 1960s were increasingly difficult to sustain economically. By 1984, he concludes, this process of intervention had to be slowed.